HUBUNGAN ANTARA KONTROL DIRI DENGAN KETERGANTUNGAN INTERNET DI PUSTAKA DIGITAL PERPUSTAKAAN DAERAH MEDAN - Juli Yanti Harahap (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
This research is aimed to see the correlation between self-control and internet depedency among teenagers. Parallel with exist theoretical basis, it can be proposed hyphotesis: there is a negative significant correlation between self-control with internet dependy in the digital libarary in the Medan Province library. To prove the hyphothesis above, product moment analysis method was use. Based on the gained data analysis there are three finding found; (1) there is a negative significant correlation between self-control and internet dependency, this result is proven with coeffesient correlation rxy= -0,123. (2) Influence from self-control toward internet dependency based on the data analysis in this study is 15,1% and the rest of it is influnced by other factors. (3) Teenager`s self-control is high, that because the gain empiric everage result is 88,80 and the hypothetical result is 72,5 while intenet depedency is high as well, as the empiric result is 107,90 and hypothetical result 72,5. From the gain study result it is generally described that teenagers have high self-control and hihgh internet depedency.